PENGARUH METODE INKUIRI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR LISTRIK STATIS DALAM PEMBELAJARAN IPA - -, Sutarto -; M, Damris -; -, Khairinal - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
The aims of this study were to answer the following questions: (1) Is there any significant influence of applying inquiry approach on students’ achievements in teaching static electricity? (2) Is there any significant influence of students’ motivation on their achievements? (3) Is there any significant influence of applying inquiry approach on students’ achievements of two groups of students owning high and low motivation? (4) Is there any interaction between inquiry approach and motivation on students’ achievements? Two groups of students of SMPN 17 Sarolangun were taught by means of inquiry and conventional approach in studying static electricity separately. A pretest and posttest were administered by means of objective tests and students’ motivation were measured by means of questionaire of Likert scale of 5. The study revealed that students’ achievements of experimental group is higher than the control group. In addition, the students with high level of motivation also showed higher achievements than the students with low level of motivation. Moreover, there is no interaction between inquiry approach and learning motivation on students’ achievements in studying static electricity. Keywords: effect of inquiry method, motivation, students’ achievements, static electricity